Ricardo Palma: three traditions and some reflections on justice, law, and literature - Távara Córdova, Francisco (2021)
The article is focused on three traditions of Ricardo Palma Soriano (1833-1919), found in his work Tradiciones peruanas: «¡A la cárcel todo Cristo!», «El corregidor de Tinta» and «Justos y pecadores». It examines how, in these traditions, the author introduces some reflections on justice. Specifically, it explains his ideas about equality before the law, that is, the justice as a practice of violence and the need for reflective and technical principles for the actors of justice to carry out their work objectively. This approach has an implicit methodological concern with law and literature. Therefore, the literary text is taken to explain its reflective potentialities about justice. Thus, categories of history, law, and literature will be used in the explanation.